Design, development and performance evaluation of a perpetual induced water wheel pumping system - KAMALKANT; SINHA, JITENDRA; SAHU, KRISHNA KANT (Journal of Soil and Water Conservation, 2026)
A water wheel pumping system with induced perpetual motion has been developed and tested. A water wheel that rotates under the action of flowing water due to its kinetic energy exerted when water strikes the face of blades, while an induced perpetual mechanism may further enhance the overall performance of the system. This innovative system demonstrates the potential of renewable energy (specifically the kinetic energy of flowing water) for water lifting and for operating drip and micro-sprinkler irrigation systems by effectively utilizing the natural flow of water. It can conserve resources, reduce dependence on conventional energy sources, and serve as a suitable alternative in remote and inaccessible areas, provided that the favourable site conditions are met. As the wheel rotates, water enters the inlet pipe, resulting in a water and air column being created within the coil due to the successive intake of water and air. Air, being compressible in nature, acts like a spring, thereby assisting in pushing the water toward the centre of the wheel and getting finally discharged through a housing pipe. The induced water pumping system was tested at a 1.2 m/s flow velocity under different operating heads for assessing its performance. When the velocity of flowing water is constant at 1.2 m/s and delivery head (total head) is varying from 3.74 m to 3.98 m, it was observed that the discharge rate of water decreases from 0.42 lps to 0.32 lps, and the RPM of the wheel also decreases from 23 to 21. It was observed that the induction of perpetual motion resulted in an increase in the RPM of the water wheel under the given flow velocity conditions. Furthermore, the most suitable way of inducing perpetual motion was achieved by fixing half-filled two-litre water bottles at 90° on both sides of the water wheel.